Wychowanie chrześcijańskie w rodzinie w dobie permisywizmu moralnego - Kluz, Marek (Śląskie Studia Historyczno-Teologiczne, 2007)
A proper education of the human being, in the age of today’s moral crisis, manifold problems and threats of the modern world, is an extremely difficult task. A Christian education is of fundamental importance here. This education is most fully realised in the family, as it is the family that influences human life to a great extent. The family is one of the most valuable things in human life, as it is the family that the happiness of individuals and the well-being of the religious and secular communities depend on. The family is of special significance to the life and development of humans. It can be said that for an individual the family is an axiological concept. This means, in the most general terms, that the family is an appropriate environment for a human to live and self-actualise as a person. It is difficult to imagine a human’s life without a family. The family is the primary and essential environment for a human to learn to be a Christian. Being a „home church”, the family is where one is taught to love God and serve other people unselfishly. It pays an important part in shaping virtues and moral attitudes. It is an environment of utmost importance in the life of every human.